Innovative Technique for Below the Knee Arterial Revascularisation Using Porcine Self Made Stapled Pericardial Tube Grafts - Elisabeth Côté; Rafael Trunfio; Celine Deslarzes-Dubuis; Kenneth Tran; Jean-Marc Corpataux; Sebastien Déglise (EJVES Vascular Forum, 2020)
Introduction: When no autologous vein is available for distal bypass in the setting of chronic limb threatening ischaemia (CLTI), new alternatives are required to solve the problems of availability, patency, and resistance to infection. An innovative technique of below the knee bypass for CLTI using a porcine self made stapled pericardial tube graft is reported. Report: An 84 year old man, admitted with right CLTI with foot infection due to long occlusion of the femoropopliteal segment, required urgent revascularisation. In the absence of autologous vein and cryopreserved vessels, a 4 mm self made stapled porcine pericardial tube graft 56 cm long was created from two 14 × 8 cm patches, to perform a femorotibioperoneal trunk bypass. On day 10, bypass thrombectomy and balloon angioplasty of the distal anastomosis were needed to treat early occlusion. Oral anticoagulation was then started. Right toe pressure increased from 0 to 70 mmHg, and no infection was reported. Complete wound healing was achieved. At six months, the bypass was still patent. Discussion: The use of porcine self made stapled pericardial tube grafts could offer new options for revascularisation in CLTI. Larger cohort studies with longer follow up are needed to confirm this successful preliminary experience.